In-Vivo AND In-Silico ANALYSIS OF ANTI-INFLAMMATORY, ANTIPYRETIC AND ANALGESIC ACTIVITY OF METHANOLIC EXTRACT OF Citrus Colocynthis - Areej Khalid; Nureen Zahra; Iqra Mushtaq; Basit Zeeshan; Abid Sarwar; Ammena Y. Binsaleh; Nawal Al-Hoshani; Maher S. Alwethaynani; Areej A Alhhazmi; Fakhria A. Al-Joufi; Tariq Aziz (Journal of the Chilean Chemical Society, 2025)
Nigella sativa (black cumin) has been used for a wide range of conditions, particularly inflammation, in traditional medical systems. Using albino rats (n = 36), the current study examines the anti-inflammatory, antipyretic, and analgesic properties of Nigella sativa methanol extract. Diclofenac and paracetamol were the typical medications used in this trial, and the four different concentrations (250, 500, 1000, and 2000 mg/kg) of the methanolic extract of Nigella sativa seeds were employed to prevent inflammation, pain, and fever. Effective antipyretic, anti-inflammatory, and analgesic inhibition were demonstrated by the methanolic extract of Nigella sativa seeds (96%, 89%, and 85%), respectively. The bioactive components found in seeds, such as thymol, p-cymene, and limonene, were also used in an in-silico study. The ligand molecules and proteins used for the anti-inflammatory, analgesic, and anti-pyretic action were 1DFN, 1A06, and 3LN0, respectively. With the specified protein, the molecular docking results were significant, and the binding energy values of the analgesic, anti-pyretic, and anti-inflammatory properties were effective. In silico and in vivo experiments, the methanolic extract of Nigella sativa seeds demonstrated efficacy against pain, inflammation, and fever.